PENGARUH PERPUTARAN MODAL KERJA TERHADAP PROFITABILITAS - Susilawati, Ewi; Fatururrahman, Mujtabah (JURNAL LENTERA AKUNTANSI, 2023)
The purpose of this study was to see the effect of working capital turnover on profitability. The population used in this study are all coal mining companies listed on the Indonesia Stock Exchange. The sampling technique used purposive sampling technique. In accordance with the predetermined criteria, there were 21 companies that entered according to the criteria and financial reporting period under study, namely 2015-2019. The type of data in this study uses secondary data obtained by the documentation method through the website www.idx.co.id. The technical analysis used in this research is simple regression analysis. The results of this study indicate that working capital turnover has a positive and significant effect on profitability. It can be seen that tcount is 4.446 and ttable is 1.65950, which means tcount> ttable (4.446> 1.65950) and the significance level is 0.000. Thus it can be stated that H0 is rejected and Ha is accepted. And the correlation coefficient value is 0.401, which means that the level of relationship between variables is moderate because it is located in the interval 0.40-0.599. And the coefficient of determination (R2) is 16.1% for profitability. While the remaining 89.9% is influenced by other factors or variables not examined in this study.Keywords: Working Capital Turnover, Profitability, Return On Assets (ROA), Coal Mining